160k views
0 votes
QF Q6.) Find the following function for a.

QF Q6.) Find the following function for a.-example-1
User Nel
by
5.9k points

2 Answers

2 votes

(f * g)(x) =\ \textgreater \ f(g(x))


f(5x^2 - 3) = 2(5x^2 - 3) - 2


f(5x^2 - 3)= 10x^2-6-2


f(5x^2 - 3)= 10x^2+(-6-2)


f(5x^2 - 3)=10x^2-8
User Tequia
by
6.0k points
2 votes
Hello!

The given equation can be rewritten to read as follows:

(f · g)(x) = f(g(x))

In other words, insert the given value of g(x) in place of the variable found in f(x) as follows:

f(5x² – 3) = 2(5x² – 3) – 2

Now simplify the right side of the equation:

f(5x² – 3) = 10x² – 6 – 2

Combine like terms:

f(5x² – 3) = 10x² – 8

We have now proven that (f · g)(x) is equal to 10x² – 8.

I hope this helps!

User Dankirkd
by
5.9k points